2022
DOI: 10.3340/jkns.2021.0289
|View full text |Cite
|
Sign up to set email alerts
|

Complex Pathophysiology of Abusive Head Trauma with Poor Neurological Outcome in Infants

Abstract: Abusive head trauma (AHT) in infants, especially acute subdural hematoma, has an extremely poor outcome. The most decisive and important finding is the appearance of a widespread low-density area on head computed tomography. This phenomenon was traditionally thought to be caused by cerebral ischemia. However, many other pathophysiological abnormalities have been found to be intricately involved. Recent studies have found that status epilepticus and hyperperfusion injures are the major causes. Another serious p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 46 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…[ 16 ] This phenomenon is unique to infant head trauma and was rarely observed in adults. [ 19 ] Brain oxygen supply-demand mismatch and systemic insults that impair oxygen delivery may contribute to the formation of BBB. [ 7 ] Recent animal studies also revealed that apnea, hypoventilation, and seizures are part of the pathophysiological cascade of the BBB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 16 ] This phenomenon is unique to infant head trauma and was rarely observed in adults. [ 19 ] Brain oxygen supply-demand mismatch and systemic insults that impair oxygen delivery may contribute to the formation of BBB. [ 7 ] Recent animal studies also revealed that apnea, hypoventilation, and seizures are part of the pathophysiological cascade of the BBB.…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] Diffuse brain injury and injury to the respiratory center are unquestionably attributable to CPA in abusive head trauma in infants. [ 18 , 19 ] Another study added three patterns of extensive low-density area, which is typical of BBB, and their pathophysiology based on when it occurs, where it occurs, and the presence of midline shift. [ 19 ] It has been demonstrated that early surgical evacuation of blood near the cerebral cortex is not protective against the development of BBB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation